Conflicts of Interest in Emergency Medicine. (16th October 2017) - Geiderman, Joel Martin; Iserson, Kenneth V.; Marco, Catherine A.; Jesus, John; Venkat, Arvind
Abstract: Conflicts of interest (COIs) are common in the practice of emergency medicine and may be present in the areas of clinical practice, relations with industry, expert witness testimony, medical education, research, and organizations. A COI occurs when there is dissonance between a primary interest and another interest. The concept of professionalism in medicine places the patient as the primary interest in any interaction with a physician. We contend that patient welfare is the ultimate interest in the entire enterprise of medicine. Recognition and management of potential, real, and perceived COIs is essential to the ethical practice of emergency medicine. This paper discusses how to recognize, address, and manage them.